Educação continuada e gerência participativa: indicadores de qualidade da gestão de recursos humanos em enfermagem - Juliani, Carmen Maria Casquel Monti [UNESP]; Kurcgant, Paulina [UNESP] (My University, 2010)
With the purpose to contribute to the construction of quality indicators in human resources management, this study aimed at identifying, from the perspective of nurse managers, essential elements in the composition of indicators for evaluating human resources management in nursing. To that end, phenomenology was adopted as the theoretical methodological framework for this qualitative investigation, in which ten nurses performing in teaching or care provision at a university hospital participated. Following approval by the Committee of Ethics in Research and the subjects’ consent, interviews were performed from September 2005 to July 2006. The analysis enabled the recovery of the following topics “Professional education”, “Training multiprofessional nursing teams” and “Institutional training conditions” in the Permanent Education category and topics “Actions that favor participant management” and “Team work” in the Participant Management category. In its conclusion, the study considers the findings to allow identify elements constituting quality indicators in human resources management.

Con la finalidad de contribuir para la construcción de indicadores de calidad en la gestión de recursos humanos, el objetivo fue identificar, desde la perspectiva de enfermeros gerentes, elementos esenciales en la construcción de indicadores para la evaluación de la calidad de gerencia de los recursos humanos en enfermería. La investigación, de naturaleza cualitativa, adoptó como referencial teórico-metodológico la fenomenología. Participaron del estudio diez enfermeros actuantes en la enseñanza o en la asistencia en un hospital de enseñanza. Tras aprobación del Comité de Ética en Investigación y consentimiento de los sujetos, fueron realizadas entrevistas entre septiembre de 2005 y julio de 2006. El análisis permitió el rescate de los temas “Formación Profesional”, “Capacitación de los Equipos de enfermería/multiprofesional” y “Condiciones Institucionales para la Capacitación” en la Categoría “Educación Permanente” y los temas “Acciones que favorecen la gerencia participativa” y “Trabajo en Equipo”, en la Categoría “Gerencia Participativa”. Como conclusión, la investigación considera que los hallazgos permiten identificar elementos constitutivos de indicadores de calidad de la gestión de recursos humanos.

Com a finalidade de contribuir para a construção de indicadores de qualidade no gerenciamento de recursos humanos, o estudo objetivou identificar, a partir da perspectiva de enfermeiros gerentes, elementos essenciais na construção de indicadores para avaliação da qualidade do gerenciamento dos recursos humanos em enfermagem. A pesquisa, de natureza qualitativa, adotou como referencial teórico-metodológico a fenomenologia. Participaram do estudo dez enfermeiros atuantes no ensino ou na assistência em um hospital de ensino. Após aprovação do Comitê de Ética em Pesquisa e consentimento dos sujeitos, foram realizadas entrevistas entre setembro de 2005 e julho de 2006. A análise permitiu o resgate dos temas “Formação profissional”, “Capacitação das equipes de enfermagem/multiprofissional” e “Condições institucionais para a capacitação” na categoria Educação permanente e os temas “Ações que favorecem a gerência participativa” e “Trabalho em Equipe”, na categoria “Gerência participativa”. Como conclusão, a investigação considera que os achados permitem identificar elementos constitutivos de indicadores de qualidade do gerenciamento de recursos humanos.
Continuing education and participant management: quality indicators of nursing human resources management
Educación continuada y gerencia participativa: indicadores de calidad de la gestión de recursos humanos en enfermería
Keywords: Quality indicators; Health care; Health manpower; Nursing; Education continuing; Indicadores de calidad de la atención de la salud; Recursos humanos en alud; Enfermería; Educación continuada; Indicadores de qualidade em assistência à saúde; Recursos humanos em saúde; Enfermagem; Educação continuada